Polysaccharide Capsule Serotype and Antibiotic Susceptibility Pattern of Streptococcus pneumoniae Clinical Isolates in Bali - Tarini, Ni Made Adi; I Putu Bayu Mayura; Ika Nurvidha Mahayanthi Mantra (Institute of Topical Disease Universitas Airlangga, 2023)
Streptococcus pneumoniae (S. pneumoniae) is a causative agent of pneumonia that can spread progressively, cause invasive disease, and increase mortality in humans. Pneumococcal or polysaccharide conjugate vaccination reduces pneumonia rates by vaccine-covered serotypes, but increases infection by non-vaccine serotypes. To determine the polysaccharide capsule serotype of S. pneumoniae isolates that cause infection at Prof. Dr. I.G.N.G. Ngoerah General Hospital and patterns of S. pneumoniae susceptibility to antibiotics from April 2017 to March 2022. All S. pneumoniae isolates from April 2017 and April 2022 were stored in STGG media in a freezer at -80 â„ƒ then subcultured on sheep blood agar. Polymerase Chain Reaction (PCR) was performed to determine pneumolysin and capsular polysaccharide serotypes of S. pneumoniae. Of the 22 isolates studied, the order of the number of serotypes from the highest was serotype 19F, 3, 6A/B, 33F, 15B/C, 4, and 6V. Seven isolates were untypeable. Antibiotic sensitivity pattern S. pneumoniae was found to be sensitive to linezolid 91%, vancomycin 86%, levofloxacin and benzylpenicillin 82%, ceftriaxone and clindamycin 73%, erythromycin 55%, and chloramphenicol 45%. Serotype 19F was identified as the most dominant capsular serotype; however, serotypes 33F and 15B/C were also found. Interestingly, the 33F serotype is not covered in the 13-valent pneumococcal conjugate vaccine (PCV13) but is covered in pneumococcal polysaccharide vaccine 23 (PPSV23), and the 15B/C serotype is not included in either PCV13 or PPSV23. The antimicrobial susceptibility patterns revealed that S. pneumoniae was susceptible to linezolid, vancomycin, benzylpenicillin, and levofloxacin.